Performance of two neuro controllers for robot path planning control - Amin, Shamsudin H. M.; Ahtiwash, O.M. (1996)
In this paper, two neuro-controllers utilizing the backpropagation algorithm are investigated for robot path tracking performance: inverse neuro-controller and neuro-emulator neuro-controller schemes. For a given task of moving a robot from a rest position to a final specified position in a minimum-time, the resulting position and velocity profiles for the investigated neuro-control models showed that, the manipulator could be moved smoothly and accurately. The tracking performance and accuracy are investigated and compared